Effect of Remote Ischemic Conditioning on Bleeding Complications in Surgery: A Systematic Review and Meta-Analysis - Krag, Andreas E.; Hvas, Christine L.; Kiil, Birgitte J.; Hvas, Anne-Mette (Seminars in Thrombosis and Hemostasis, 2021)
Remote ischemic conditioning (RIC) is administered with an inflatable tourniquet by inducing brief, alternating cycles of limb ischemia and reperfusion. RIC possibly impacts the hemostatic system, and the intervention has been tested as protective therapy against ischemia-reperfusion injury and thrombotic complications in cardiac surgery and other surgical procedures. In the present systematic review, we aimed to investigate the effect of RIC on intraoperative and postoperative bleeding complications in meta-analyses of randomized controlled trials including adult patients undergoing surgery. A systematic search was performed on November 7, 2020 in PubMed, Embase, and the Cochrane Central Register of Controlled Trials. Randomized controlled trials comparing RIC versus no RIC in adult patients undergoing surgery that reported bleeding outcomes in English publications were included. Effect estimates with 95% confidence intervals were calculated using the random-effects model for intraoperative and postoperative bleeding outcomes. Thirty-two randomized controlled trials with 3,804 patients were eligible for inclusion. RIC did not affect intraoperative bleeding volume (nine trials; 392 RIC patients, 399 controls) with the effect estimate −0.95 [−9.90; 7.99] mL (p = 0.83). RIC significantly reduced postoperative drainage volume (seven trials; 367 RIC patients, 365 controls) with mean difference −83.6 [−134.9; −32.4] mL (p = 0.001). The risk of re-operation for bleeding was reduced in the RIC group (16 trials; 838 RIC patients, 839 controls), albeit not significantly, with the relative risk 0.65 [0.39; 1.09] (p = 0.10). In conclusion, RIC reduced postoperative bleeding measured by postoperative drainage volume in this meta-analysis of adult patients undergoing surgery.
Keywords: red blood cell; surgical; ischemic preconditioning; postoperative bleeding; surgical procedures; postoperative complication